Creative Thinking Skills in Science Education: A Prisma-based Systematic Literature Review - Laila Puspita; Abdurrahman Abdurrahman; Tri Jalmo; Dina Maulina; Komarudin Komarudin; Suherman Suherman; Nurrana Fitria Luthfi (CV FOUNDAE, 2025)
Creative thinking skills are widely discussed in science education research, yet their conceptualization, pedagogical treatment, and measurement still show methodological diversity. This study systematically synthesizes recent studies on creative thinking skills in science education, focusing on learning strategies, learning media, and assessment instruments. A systematic literature review (SLR) using the PRISMA framework was conducted on 23 Scopus-indexed publications from 2019–2022. The results indicate that most studies position creative thinking skills as a learning outcome embedded in instructional innovation rather than as an independent construct. STEM-oriented learning, technology-assisted learning, problem-based learning, and inquiry-based learning are the most frequently explored contexts. However, the literature is dominated by qualitative and descriptive research, with limited comparative or experimental evidence. Variation in definitions and measurements also persists, often overlapping with related constructs such as critical thinking. Overall, this review reveals rich pedagogical innovation but limited methodological consistency and analytical rigor. The findings highlight the need for clearer construct boundaries, more robust research designs, and better alignment between learning strategies and validated instruments. This review contributes to mapping research patterns and identifying gaps for future empirical studies in creative thinking skills in science education